Is research on SMEs in Malaysia an utter waste of time?: A literature review - Jaafar, Abdul Rahman; Baharom, Nuraishani; Sharif, Mohmad Yazam (2014)
This paper reviews some important literature on small and medium scale enterpisies (SMEs) in Malaysia.It was observed that the focus of research on the SMEs was taken from four perspectives – management, finance, marketing and technology.Scholars have looked at issues of managing organizational resources such as human resources, internationalization, total quality management (TQM), technology management and information and communication technology (ICT).But less attention was given by them on issues relating to SME firm performance and firm effectiveness.These two issues are critical in a very special way as they affect the existence and continued survival of SME firms.